2002
DOI: 10.1038/sj.onc.1205136
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-like effects of thyroid hormone on the regulation of tumor suppressor proteins, p53 and retinoblastoma, in breast cancer cells

Abstract: T47D cells represent an estrogen-responsive human ductal carcinoma cell line which expresses detectable levels of estrogen receptor (ER). We have previously shown that estradiol (E 2 ) treatment of T47D cells causes an increase in the level of p53 and a concomitant phosphorylation of retinoblastoma protein (pRb). In the present study, we have analysed the expression of p53 and phosphorylation state of pRb and compared the eects of E 2 and triiodothyronine (T 3 ) on these phenomena. Cells were grown in a medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 34 publications
6
101
2
1
Order By: Relevance
“…Alternatively, thyroid hormones might stimulate the transcription of ERß-dependent genes through a combination of ERß-TRα1, as suggested by Vasudevan et al (5). Dinda et al (17) postulated that the estrogen-like effects of T 3 were mediated by TR interaction with ER response element. Therefore, another possibility is that T 3 bound to the T 3 receptor, independently of ER, stimulates ER response element function, promoting transcription of target genes that lead to cellular proliferation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternatively, thyroid hormones might stimulate the transcription of ERß-dependent genes through a combination of ERß-TRα1, as suggested by Vasudevan et al (5). Dinda et al (17) postulated that the estrogen-like effects of T 3 were mediated by TR interaction with ER response element. Therefore, another possibility is that T 3 bound to the T 3 receptor, independently of ER, stimulates ER response element function, promoting transcription of target genes that lead to cellular proliferation.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, physiological concentrations of T 3 , the more active form of thyroid hormone, significantly enhance estradiol growth stimulation of a number of human breast carcinoma cell lines (16). In T47D breast cancer cells, E 2 and T 3 similarly regulate cell cycle progression and proliferation raising the p53 level and causing hyperphosphorylation of pRb (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite extensive population studies, the results as a whole have been inconsistent. In preclinical models, it has been found that T3 may sustain serum-free proliferation of several cell lines, including breast cancer; in addition, rodent mammary gland development and physiology have been found to be sensitive to T3 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, HTs podem alterar a transcrição de genes ERdependentes, através da ligação ERTR, como sugerido por Vasude van e cols. (36) ou ainda ocorrer interação entre TR e elementos responsivos do ER (37). De qualquer for ma, essas interações indicam que, em estado de pós menopausa com níveis baixos de E2, os HTs podem levar ao crescimento tumoral estimulando vias de ação pertencentes aos hormônios estrogênicos.…”
Section: Resultsunclassified